Why should I Trust You? A Survey on Interpersonal Trust in Virtual Learning Environments - Barbosa, Marcelo Pereira; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na Educação, 2024)
One significant challenge of e-learning is enabling collaborative learning on its platforms. Trust among students is essential for student interaction in collaborative academic activities. Nevertheless, building trust is a complex and dynamic process, and factors for acquiring trust in virtual learning environments remain a subject of ongoing investigation. In order to contribute to identifying some factors that influence the acquisition of trust among students in VLEs, we surveyed 119 students. The results revealed several characteristics influencing trust acquisition. Over 90 personal attributes were identified as capable of influencing trust among students, with "commitment," "participation," and "meeting deadlines" identified as a triad of the most influential trust factors